Reassessing the Effects of Corporate Income Taxes on Mergers and Acquisitions Using Empirical Advances in the Gravity Literature - Sebastien Bradley; Federico Carril-Caccia; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the relationship between corporate income taxes and mergers and acquisitions (M&As). To this end, we compile and deploy a dataset consisting of all cross-border and domestic M&A deals for 118 source (acquirer) and 122 destination (target) countries and 84 sectors over the period 1995-2019. From a methodological perspective, we implement leading methods from the empirical gravity literature on trade, foreign direct investment, and migration, and we demonstrate their importance for estimating the impact of corporate income taxes on cross-border versus domestic M&A activity. Our main finding is that a one percentage point increase in target country corporate income tax rates decreases the number of cross-border acquisitions by about 0.8 percent relative to domestic M&As. This result is robust to various sensitivity checks and is comparable to previously published estimates. Nevertheless, our stepwise estimation strategy exemplifies the importance of individual empirical refinements. These should serve as the basis for future work investigating the effects of taxation on bilateral flows.
Keywords: F10; F14; F21; F23; H25; H87; 330; corporate income taxes; mergers and acquisitions; gravity methods